Analysis of Income from Palm Sugar Artisans in Makmur Village, Palolo District, Sigi Regency - Hafista, Salmah; Yunus, Rita; Sading, Yunus; Haprin, Nuryana; Lutfi, Muhtar (Golden Ratio of Data in Summary, 2024)
This research aims to find out how much Palm Sugar Craftsman earn per month in Makmur Village, the research method is the method used in this research is the qualitative descriptive analysis method. By using primary data sources and secondary data. Data analysis in this research uses the income and revenue analysis method. Based on the results of research in Makmur Village the conclusion is that the income or profit results were IDR 1.098.335. From the receipt of IDR 1.710.000 from sales of Palm Sugar for ninenty pieces of Palm Sugar for a month, valued at eighteen thousand rupiah, the total costs of IDR 611.665 was obtained from fixed costs plus variable costs. To get income or profit, use TR-TC or 1.710.000-611.665 so you will get a result of IDR 1.108.335. The results of the R/C Ratio analysis show that the Palm Sugar business in Makmur Village provides profits with an R/C value shows that the Palm Sugar business in Makmur Village, Palolo District is worth running.